A Characteristics of Milk Caramel Candy with the Addition of Stevia (Stevia Rebaudiana Bertoni) Extract Leaf Powder - Yola Andriani; Daimon Syukri; Rini Rini (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2022)
The aime of this study was to determine the characteristics of milk caramel candy with the addition of stevia extract leaf powder (Stevia rebaudiana Bertoni) based on the physical, chemical properties, and level of acceptance of the panelists for milk caramel candy. The addition of stevia extract leaf powder to the milk caramel candy was expected to be reduce the value. This study used a completely randomized design (CRD) with 5 treatments and 3 replications. Data analysis using ANOVA and further testing of DNMRT at a 5% significance level. The treatments in this study were the level of addition of stevia extract leaf powder is A (0%), B (0.1%), C (0.2%), D (0.3%), and E (0.4%). The results showed that the addition of different stevia extract leaf powders in milk caramel candy was significantly different at the 5% level on the analysis of the water content, protein content, energy, antioxidant activity, color analysis, organoleptic tests (color, and taste) and the level of addition of stevia extract leaf powder was not significantly different at the 5% level on ash content, fat content, reducing sugar, hardness analysis and organoleptic (aroma and texture) analysis. The best treatment in this study was addition of 0.2% stevia extract leaf powder, the results of chemical analysis showed that the average water content was 9.28%, ash content was 1.87%, protein was 13,91%, fat was 9,69%, reducing sugar was 8.21%, energy value (calories) 403,86 cal/g, antioxidant activity 43.04%, physical analysis of hardness 89.40 N/cm2, color 126.88 ºHue, and organoleptic test results were color 4.35 (like), aroma 3.65 (like), taste 4.25 (like), and texture 3.85 (like).